Genome Sequences of a Plant Beneficial Synthetic Bacterial Community Reveal Genetic Features for Successful Plant Colonization - de Souza, Rafael Soares Correa; Armanhi, Jaderson Silveira Leite; Damasceno, Natália de Brito; Imperial, Juan; Arruda, Paulo (Frontiers in Microbiology, 2019)
Despite the availability of data on the functional and phylogenetic diversity of plant-associated microbiota, the molecular mechanisms governing the successful establishment of plant bacterial communities remains mostly elusive. To investigate bacterial traits associated with successful colonization of plants, we sequenced the genome of 26 bacteria of a synthetic microbial community, 12 of which displayed robust and 14 displayed non-robust colonization lifestyles when inoculated in maize plants. We examined the colonization profile of individual bacteria in inoculated plants and inspected their genomes for traits correlated to the colonization lifestyle. Comparative genomic analysis between robust and non-robust bacteria revealed that commonly investigated plant-growth promoting features such as auxin production, nitrogen fixation, phosphate acquisition, and ACC-deaminase are not deterministic for robust colonization. Functions related to carbon (C) and nitrogen (N) acquisition, including transporters of carbohydrates and amino acids, kinases involved in signaling mechanisms associated to C and N uptake, were enriched in robust colonizers. While enrichment of carbohydrate transporters was linked to a wide range of metabolites, amino acid transporters were primarily related to the uptake of branched-chain amino acids. Our findings identify diversification of nutrient uptake phenotypes in bacteria as determinants for successful bacterial colonization of plants.